The Truths of Psychoanalysis. - Feyaerts, Jasper (Figures of the unconscious., 2022)
Truth has always been a central philosophical category, occupying different fields of knowledge and practice. In the current moment of fake news and alternative facts, it is mandatory to revisit the various meanings of truth. Departing from various approaches to psychoanalytic theory and practice, the authors gathered in this book offer critical reflections and insights about truth and its effects. In articulations of psychoanalysis with (for instance) philosophy, ethics and politics, the reader will find discussions about issues such as knowledge, love, and clinical practice, all marked by the matter of truth.